Resolving the Disk-Halo Degeneracy: A look at M74. Issue Volume 11:Issue S321(2015) (21st March 2017) - Aniyan, S.; Freeman, K. C.; Arnaboldi, M.; Gerhard, O.; Coccato, L.; Kuijken, K.; Merrifield, M.
Abstract: The decomposition of the 21 cm rotation curve of galaxies into contribution from the disk and dark halo depends on the adopted mass to light ratio (M/L) of the disk. Given the vertical velocity dispersion (σ z ) of stars in the disk and its scale height ( h ), the disk surface density and hence the M/L can be estimated. Earlier works have used this technique to conclude that galaxy disks are submaximal. Here we address an important conceptual problem: σ z and h must pertain to the same population. Our analysis concludes that previous studies underestimate the disk surface mass density by ~ 2, sufficient to make a maximal disk for M74 appear like a submaximal disk.